1966
DOI: 10.1002/app.1966.070100208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and degradation of poly (alkyl α‐cyanoacrylates)

Abstract: SynopsisI n order to study structure-tissue reactivity relationships arid ultimately develop a less necrotizing adhesive, this laboratory undertook a study of the synthesis and degradation of the homologous series of a-cyanoacrylate monomers and polymers. A method for synthesizing high purity cyanoacrylates and some of their chemical and physical properties are presented. In vitro kinetics studies under heterogeneous and homogeneous conditions indicate that cyanoacrylate polymers degrade by hydrolytic scission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
3

Year Published

1966
1966
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(85 citation statements)
references
References 4 publications
5
77
0
3
Order By: Relevance
“…It is likely that utilization of Fe 3 O 4 MNPs as drug carriers may overcome the physiologic limitations of drug transport by capillary barriers. 17 Currently, the mechanism by which nanoparticles traverse the barrier is unclear. 18 Although iron oxide nanoparticles are known to be well tolerated by the body and degrade with time, 19 it is worthwhile verifying whether the structure of Fe 3 O 4 MNPs changes after digestion and absorption through the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that utilization of Fe 3 O 4 MNPs as drug carriers may overcome the physiologic limitations of drug transport by capillary barriers. 17 Currently, the mechanism by which nanoparticles traverse the barrier is unclear. 18 Although iron oxide nanoparticles are known to be well tolerated by the body and degrade with time, 19 it is worthwhile verifying whether the structure of Fe 3 O 4 MNPs changes after digestion and absorption through the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In an aqueous medium, and especially in biological fluids, the degradation of PACA nanoparticles is thought to result from solubilization of the polymer because of hydrolysis of lateral ester bonds (Leonard et al, 1966). Indeed, such hydrolysis leads to the appearance of carboxylic groups.…”
Section: Spectroscopic Analysesmentioning
confidence: 99%
“…In addition to the above, a rapid depolymerizationrepolymerization mechanism described by Ryan et al degrades PBCA by base-induced depolymerization, yielding lower molecular weight oligomers 26 ( Figure S7), and an alternative mechanism based on the inverse Knoevenagel reaction has also proposed. 27 Lenaerts et al have shown that this route of degradation played a marginal role when compared with the enzymatic route of degradation. 28 The influence of pH on degradation of poly(alkylcyanoacrylates) has also been studied in detail, eg, in the work of Scherer et al 25 The degradation rate increased with increasing pH; however, after uptake in cells via the endocytotic pathway, the pH will decrease from early endosomes to lysosomes, making this route of degradation less likely.…”
mentioning
confidence: 99%